Mendampingi Siswa untuk Mengenal dan Memahami Surat Pribadi dan Surat Dinas pada Kelas VII MTs NU Umbul Sari - Sugiarti Sugiarti; Genli Wahyu Saputra (Jurnal Pengabdian Masyarakat (abdira), 2022)
The purpose of assisting students to recognize and understand personal letters and official letters in class VII MTs NU Umbul Sari so that students recognize and understand the content, structures of personal letters and official letters. The method that will be used in carrying out community service activities is direct observation at the MTs NU Umbul Sari school, then followed by activities to assist students to recognize and understand personal letters and official letters in class VII MTs NU Umbul Sari. Observation or observation is an activity towards a process or object with the intention of feeling and then understanding the knowledge of a phenomenon based on previously known knowledge. The result is that there is a process of improving students in understanding the content, and structure of personal and official letters